2017
DOI: 10.1136/bcr-2016-218281
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic resuscitation with Intralipid in an epinephrine unresponsive cardiac arrest following overdose of amitriptyline and propranolol

Abstract: Amitriptyline and propranolol are life threatening in overdose. The efficacy of intravenous lipid emulsion (ILE) in tricyclic antidepressant and propranolol overdose is unclear. We report a dramatic response to ILE following pulseless electrical activity arrest due to mixed amitriptyline and propranolol overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…Interestingly, our findings of modest, gradual effects appear in contrast to the rapid effects (i.e., within minutes) often reported in case reports, in which other modalities (e.g., fluids and inotropes) were always used before and alongside ILE and may likely have contributed to the beneficial effects attributed to ILE. The primary proposed mechanism behind rapid effects of ILE insert (i.e., the reversal of toxicity through binding of the poison intravascularly in a lipid compartment) is therefore not likely to play any role in our study.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, our findings of modest, gradual effects appear in contrast to the rapid effects (i.e., within minutes) often reported in case reports, in which other modalities (e.g., fluids and inotropes) were always used before and alongside ILE and may likely have contributed to the beneficial effects attributed to ILE. The primary proposed mechanism behind rapid effects of ILE insert (i.e., the reversal of toxicity through binding of the poison intravascularly in a lipid compartment) is therefore not likely to play any role in our study.…”
Section: Discussioncontrasting
confidence: 93%
“…The American College of Medical Toxicology also regards ILE as a potential option for severe poisonings with lipophilic drugs if patients are hemodynamically unstable and not responsive to standard resuscitation measures . Thus, use of ILE has expanded to severe poisonings with other drugs than local anesthetics (e.g., β‐blockers) in which beneficial effects also have been reported in animal models and clinical case reports . However, the overall quality of evidence concerning use of ILE for other indications than local anesthetic poisoning is low, and systematic reviews of case reports of poisonings find contradictory interpretations of available case data .…”
mentioning
confidence: 99%
“…A recent systematic review of non-local anesthetic drug toxicity treated with ILE reported several cases of ILE use in propranolol overdose with mixed response but no cases of tizanidine toxicity managed with ILE [3,[7][8][9][10][11][12]. Our case is distinct from the existing literature in that he did not have cardiac arrest or pressor requirement prior to receiving ILE.…”
Section: Discussionmentioning
confidence: 52%
“…8 Sebe et al 5 reported a series of 15 adult patients who were treated with ILI secondary to BB, CCB, and paracetamol intoxication, 14 of them recovered, whereas one patient died. Le Fevre et al 9 reported a case of a 25-year-old patient with a dramatic response to ILI following pulseless electrical activity arrest due to a mixed amitriptyline and propranolol overdose. Amanda et al 10 reported a complete clinical recovery with the administration of ILE in combination with high-dose insulin (HDI) in a 7-month-old symptomatic pediatric patient with acute propranolol toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,11 Kolcz et al11 reported a case of 15-year-old girl with cardiogenic shock after alcohol, propranolol and verapamil overdose. Their patients successfully recovered with ECPR and PEX.…”
mentioning
confidence: 99%